Profil Kemampuan Guru dalam Mengimplementasikan Pembelajaran Karakter di Sekolah Dasar Negeri - Nana Suryana; Wahyu Sopandi; Dasim Budimansyah; Yadi Ruyadi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2025)
Strengthening character education in Indonesia is a major concern in efforts to form a generation of the nation with morals. This study aims to describe the ability of teachers in implementing character learning in the classroom. The subjects of the study were elementary school teachers in Cluster IV, Pagerageung District, Tasikmalaya Regency. The method used was quantitative descriptive. The sample was 36 people. Data were collected through a closed questionnaire that measured three main aspects; the ability to plan, implement, and evaluate character learning. The results showed that the ability of teachers in planning character learning was in the good category (52.87%), the implementation of character learning was also good (66%), and the evaluation of character learning was classified as very good (80.35%). Supporting factors for the success of character learning include student motivation, support from the school community, and the role of the family environment. The obstacles found included the difficulty of integrating character values ​​into materials, methods, strategies, and learning media. These findings emphasize the central role of teachers in strengthening character education and the need for support from various parties to increase the effectiveness of the implementation of character learning in elementary schools.